Needlessly controversial: the reporting of pharmaco- and psycho-therapy for the treatment of depression in the UK media. Issue 16 (29th December 2021) - Pathak, Anushka; Lim, Elizabeth; Lawrie, Stephen
Abstract: Background: It is well-established that media influences public perceptions, and that media coverage of psychiatry is negative compared to the rest of medicine. No studies that we know of, have compared media reporting on antidepressants and talking therapies as treatments for depression. We hypothesised that coverage of antidepressants would be more negative than that of psychotherapies in both headlines and articles. Methods: We identified online articles in The Sun, Daily Mirror, Daily Mail, Daily Express, and The Guardian between 11 June 2013 and 11 June 2018. Two raters independently evaluated their titles/content with regard to their portrayal of antidepressants and psychotherapies (positive/negative/neutral), with good inter-rater reliability. Results: We identified 221 articles. Antidepressants featured in 184 articles, of which 27 (15%) portrayed them positively, 68 (37%) negatively, and 89 (48%) neutrally; and 173 headlines, of which 24 (14%) portrayed them positively, 64 (37%) negatively, and 85 (49%) neutrally. Antidepressants received more coverage than psychotherapy, which featured in 132 articles, of which 48 (36%) portrayed them positively, 3 (2%) negatively, and 81 (61%) neutrally; and 53 headlines, of which 16 (30%) portrayed them positively, 2 (4%) negatively, and 35 (66%) neutrally. A Fisher's exact test revealed a statistically significant difference between the portrayal of antidepressants and psychotherapies in both articles ( p = 2.86 × 10 −15 ) and headlines ( p = 2.79 × 10 −6 ). Conclusion: Despite the two treatments being similarly effective, the portrayal of antidepressants in the UK online media is more negative than that of psychotherapy. This could potentially discourage patients from considering taking antidepressants, and provoke patients currently taking antidepressants to stop abruptly.